Applying a Motivational Instructional Design Model to Stroke Rehabilitation: A Feasibility Study on Occupational and Swallowing Therapies - Kazuaki Oyake, PT, PhD; Shota Watanabe, OT, MSc; Ayano Takeuchi, ST, BSc; Taiki Yoshida, OT, PhD; Takashi Shigematsu, MD, PhD; Yuuki Natsume, ST, BSc; Shigeki Tsuzuku, MD, PhD; Kunitsugu Kondo, MD, PhD; Ichiro Fujishima, MD, PhD; Yohei Otaka, MD, PhD; Satoshi Tanaka, PhD (Archives of Rehabilitation Research and Clinical Translation, 2024)
Objective: To investigate the feasibility of poststroke interventions using a motivational instructional design model with occupational therapy (OT) and swallowing therapy (ST) and the model's potential physical and mental health effects. Design: An open-label, single-arm, feasibility study on the Attention, Relevance, Confidence, and Satisfaction model. Setting: Two convalescent rehabilitation wards. Participants: Twenty-five patients with stroke (N=25) (19 men; mean age, 62.4±11.9y; 61.9±36.8d from the first stroke) were recruited. Interventions: Twelve participants received a motivational approach based on the Attention, Relevance, Confidence, and Satisfaction model during OT (OT group), and 13 received it during ST (ST group). The intervention lasted 40-60 minutes daily, 5 days weekly, for 4 weeks. Main Outcome Measures: The primary outcomes included the dropout rate, an adverse event, and the participants’ acceptability of the intervention. Paretic arm function was assessed in the OT group; swallowing ability was assessed in the ST group; and activities of daily living, depressive symptoms, and apathy were assessed in both groups. Results: No participants dropped out of the intervention or experienced an adverse event. Twenty-one participants (84%) were satisfied with the intervention, and 19 (76%) hoped to continue receiving it. The OT group showed statistically significant improvements in paretic arm function and activities of daily living (Cohen's r=0.68-0.77), whereas the ST group improved in swallowing ability, activities of daily living, and depressive symptoms (Cohen's r=0.62-0.85). Conclusions: The interventions using the motivational instructional model with OT and ST were feasible and could improve poststroke paretic arm function, swallowing ability, and activities of daily living after stroke.